(untitled) (Journal of the College of Education for Women, 2022)
Recently, women’s rape has been a pervasive problem in the Iraqi society. Thus, it has become necessary to consider the role of language and its influence on the common beliefs and opinions about rape in the Iraqi society. Thus, taking into consideration the critical role of language and its impact on the perception of human reality and the social development based on people’s beliefs and principles of life has become highly indispensable. Therefore. The aim of this article is to address this problem critically from legislation and social norms in NGOs’ reports (2015; 2019) with reference to some provisions from the Iraqi Panel Code (1969; 2010). Therefore, the researchers examine the discursive strategies and ideological viewpoints in the selected data through the employment of critical discourse analysis. Specifically, the researchers have adopted van Dijk’s (2011) socio-cognitive approach and van Dijk’s (2000) ideological model to show how language produces and reproduces domination and abuse of power, engendering as a result injustice and inequality. The study has concluded that the NGOs’ reports are written in a language that reflects the attitudes and opinions which might be shared among group members. These reports rely heavily on the linguistic device that is of evidentiality to assure the credibility of giving evidence about the domination of social norms in relation to women’s rape. More importantly, the dichotomy of positive and negative representation is highly adopted as an ideological strategy, showing the conflict between the legislation and social norms. Therefore, the study has recommended that the government in its legal institutions should provide provisions to protect the raped women from society and from their families.